Erneuerbare Energien für Regionen Flächenbedarfe und Flächenkonkurrenzen - Dumke, Hartmut (TU Wien Academic Press, 2020)
Every human action consumes energy: heating, cooling, hot water, electricity and transport requirements - all of these require energy. But climate change demands that our energy needs also change, that we use more and more renewable energies and less and less C02. To do this, we must look at area requirements. In other words, what area per energy quantity per year does a renewable energy source require? Which sources require additional sealing and land use? How strongly does the production of renewable energy compete with other area and land uses? And what are the consequences for spatial and regional planning? The following publication will help answer these questions by providing a catalogue of area requirements for renewable energy sites. In addition, it makes clear that achieving integrated and regional energy planning involves not only energy technology, but requires further research into planning and participation processes. The concept of a regional cooperation area shows great potential in this aspect